4CPS-101 Trifluridine–tipiracil for metastatic colorectal cancer: real world data experience. (24th March 2020) - Tonelli, M; Scaldaferri, M; Bustreo, S; Fanchini, L; Ritorto, G; Racca, P; Cattel, F
Abstract : Background and importance: Colorectal cancer represents a major health problem in developed countries. Median age at diagnosis is about 70 years. This creates new challenges in antineoplastic treatment, taking into consideration the characteristics of this group of patients: functional alterations that increase the toxicity of drugs, high comorbidity and polypharmacy. Trifluridine–tipiracil is an oral antineoplastic agent consisting of trifluridine and tipiracil. Tipiracil blocks the degradation of trifluridine by thymidine phosphorylase, which improves the bioavailability of trifluridine and allows for oral administration. A phase III study comparing trifluridine–tipiracil versus placebo in patients with metastatic colorectal cancer (mCRC) refractory to or intolerant t standard therapy (n=800) showed a modest benefit in overall survival and progression free survival compared with placebo. Aim and objectives: To assess the efficacy and safety of trifluridine–tipiracil in a cohort of 49 patients with mCRC treated in our institution. Material and methods: This was an observational retrospective study of patients treated with trifluridine–tipiracil as monotherapy from March 2018 to September 2019. The data collected, obtained from the electronic medical records, were sex, age, previous chemotherapy regimens, treatment duration and reason for discontinuation, adverse events and follow-up data. Results: Forty-nine patients, 33 men (67%), with a median age of 64 years (41–84), were treated with trifluridine–tipiracil monotherapy. The median number of previously administered chemotherapy regimens was 2, while trifluridine and tipiracil was administered for a median of 3 cycles. At evaluation after 3 cycles, 53% of patients showed progression of disease, 8% mixed response of metastatic site, 2% partial response and 4% stable disease. For 32% of patients the response was not evaluated due to early progression of disease or patients lost to follow-up. Twenty-four patients (49%) underwent subsequent therapies after treatment with trifluridine–tipiracil, mainly with raltitrexed (12 patients/50%), regorafenib and mitomycin C (3 patients/12%). Adverse events occurred in 23 patients (47%): haematological events (n=14, 47%), asthenia (n=7, 30%), dyspnoea (n=2, 9%) and hyperbilirubinaemia (n=1, 4%). Conclusion and relevance: Our data confirmed the modest benefits for highly pretreated patients, consistent with previously published clinical trials. References and/or acknowledgements: 1. Mayer RJ, et al. Randomized trial of TAS-102 for refractory metastatic colorectal cancer. N Engl J Med 2015;372:1909–1919. No conflict of interest.